Biopsychosocial factors associated with complaints of dizziness in older adults with Type 2 Diabetes Mellitus - Eliza Mikaele Tavares da Silva; Bartolomeu Fagundes de Lima Filho; Vanessa da Nóbrega Dias; José Diniz Júnior; André Gustavo Pires de Sousa; Juliana Maria Gazzola (Revista Brasileira de Geriatria e Gerontologia, 2020)
Abstract Objective: To analyze the biopsychosocial factors associated with complaints of dizziness in older adults with Type 2 Diabetes Mellitus. Methods: A cross-sectional, descriptive study with a sample selected for convenience was performed in a university hospital. The participants were individuals aged 60 years or older diagnosed with type 2 Diabetes Mellitus. Patients were assessed using a multidimensional survey, containing sociodemographic, clinical-functional, psycho-psychological and cognitive data. The Mini-Mental State Exam and the Short Geriatric Depression Scale (GDS-15) were used to screen for cognitive deficits and depressive symptoms, respectively, and the Timed Up and Go Test was used to assess mobility. Data analysis was performed using the Chi-square and Mann-Whitney tests. Results: The sample consisted of 157 older adults of whom 45.22% complained of dizziness. There was a statistically significant association between dizziness and the variables: female sex, being unmarried, a low level of education, a negative self-perception of general health and vision, complaints of pain in the lower limbs, a fear of falling, a tendency to fall, cognitive impairment and psychological symptoms. Conclusion: Knowledge of the factors associated with the complaint of dizziness in older adults with DM2 allows improved targeting of prevention, assessment and intervention actions, in order to minimize the occurrence of falls, maintain or optimize functional capacity and cognitive skills, and thus improve quality of life.